Positive and negative control of the skeletal alpha-actin promoter in cardiac muscle. A proximal serum response element is sufficient for induction by basic fibroblast growth factor (FGF) but not for inhibition by acidic FGF. - Parker,TG; Chow,KL; Schwartz,RJ; Schneider,MD (J Biol Chem, 1992)
Like mechanical load in vivo, basic fibroblast growth factor (bFGF) selectively provokes cardiac expression of "fetal" genes including skeletal alpha-actin (SkA). Antithetically, acidic FGF (aFGF) suppresses SkA transcription. To define sites controlling SkA transcription in cardiac muscle cells, rat cardiac myocytes were transfected with internal-deletion and block-substitution mutations in the SkA promoter, including three motifs resembling the fos serum response element (SRE). The upstream, central, and proximal SREs each contributed to basal expression in cardiac myocytes. To determine whether identical elements mediate induction by bFGF versus inhibition by aFGF, the proximal SRE (SRE1) and fos SRE were positioned upstream from a neutral promoter. In cardiac myocytes, both the SRE1 and fos SRE were expressed at levels up to one-third that of the SkA promoter (nucleotides -202 to -11). Neither was expressed in quiescent cardiac fibroblasts. bFGF augmented SRE1-CAT activity, whereas aFGF produced no change; the fos SRE was induced by both. The transcriptional and mitogenic actions of aFGF were contingent on the presence of a putative nuclear translocation motif. Thus 1) the SkA SRE1 and fos SRE each suffice for tissue specificity in cardiac myocytes; 2) unlike the c-fos SRE, the SkA SRE1 is induced selectively by bFGF yet not aFGF; 3) sequences alternative or in addition to the SRE1 are obligatory for aFGF to suppress the SkA promoter; and 4) possible differences in intracellular localization are one basis for divergent actions of aFGF and bFGF in cardiac muscle cells.